(untitled) (Global Journal of Management and Business Research, 2021)
Entrepreneurship is a process of creating a new business to produce and market new, innovative or existing product. Small business is a bridge for entrepreneurs to perform. Even though entrepreneurial competencies and entrepreneurial orientation have been considered separately on small business performance, little research attention has been given to the theoretical mix of entrepreneurial competencies and entrepreneurial orientation in a single research work. Very few studies have been considered dynamic capabilities as a mediator and external environment as a moderator to facilitate the relationships between entrepreneurship and business success.